A Kunitz proteinase inhibitor (HcKuPI) participated in antimicrobial process during pearl sac formation and induced the overgrowth of calcium carbonate in Hyriopsis cumingii. Issue 89 (June 2019) - Jin, Can; Liu, Xiao-Jun; Li, Jia-Le
Abstract: Proteinase inhibitors with the ability to inhibit specific proteinases are usually closely connected with the immune system. Interestingly, proteinase inhibitors are also a common ingredient in the organic matrix of mollusk shells. However, the molecular mechanism that underlies the role of proteinase inhibitors in immune system and shell mineralization is poorly known. In this study, a Kunitz serine proteinase inhibitor (HcKuPI) was isolated from the mussel Hyriopsis cumingii . HcKuPI was specifically expressed in dorsal epithelial cells of the mantle pallium and HcKuPI dsRNA injection caused an irregular surface and disordered deposition on the aragonite tablets of the nacreous layer. These results indicated that HcKuPI plays a vital role in shell nacreous layer biomineralization. Moreover, the expression pattern of HcKuPI during LPS challenge and pearl formation indicated its involvement in the antimicrobial process during pearl sac formation and nacre tablets accumulation during pearl formation. In the in vitro calcium carbonate crystallization assay, the addition of GST-HcKuPI increased the precipitation rate of calcium carbonate and induced the crystal overgrowth of calcium carbonate. Taken together, these results indicate that HcKuPI is involved in antimicrobial process during pearl formation, and participates in calcium carbonate deposition acceleration and morphological regulation of the crystals during nacreous layer formation. These findings extend our knowledge of the role of proteinase inhibitors in immune system and shell biomineralization. Highlights: HcKuPI is involved in antimicrobial process during pearl sac formation. HcKuPI is specifically expressed in dorsal epithelial cells of the mantle pallium. HcKuPI dsRNA injection caused disordered aragonite tablets deposition of the nacreous layer. GST-HcKuPI could increase precipitation and induce overgrowth of calcium carbonate.